The effectiveness of acceptance- and commitment-based therapy on perception of disease in patients with irritable bowel syndrome - Sedighe Aghalar; Fardin Moradi Manesh; Naser Saraj Khorami; Fariba Hafezi (International Archives of Health Sciences, 2020)
Aims: The purpose of this study was to investigate the effectiveness of acceptance and commitment therapy on perception of disease in patients with irritable bowel syndrome (IBS). Materials and Methods: The quasi-experimental research method was pretest and posttest with control group. The statistical population of this study included patients with irritable bowel syndrome (IBS) in Semirom city which were selected 30 of whom through purposive sampling and randomly assigned to two groups (Acceptance and commitment Therapy (ACT) and control group). Before and after the intervention, the individuals in all two groups were evaluated with the Disease Perception Scale. Then, there was a weekly session acceptance and commitment therapy based on treatment protocols for IBS for the experimental group, and the control group received no intervention. Results: The findings showed that acceptance and commitment therapy had significant effects on the components of illness sequences (P < 0.001), personal control (P < 0.001), nature of illness (P < 0.001), control through treatment (P < 0.001), worrying about illness (P = 0.002), and affectional respond to illness (P < 0.001). Conclusion: In according to findings, it can be concluded that the acceptance and commitment therapy as an effective treatment can be used in acute disease situations for people to promote positive perception of their illness.